The Impact of Computer- Based Video-games Devices on the Children's Health - Melad Faiq Jamel; Wesam Saadoon Shafiq; Salwa Sh Abdul-wahid (Diyala Journal of Medicine, 2019)
Background: Computer video games require great attention and focus, the more exposure to interactive media, the more exposure to challenges that will recommend players to play better and gain more intelligence.